Donation after Circulatory Death: An Updated Description of the European Landscape. (July 2018) - del Mar Lomero, Maria; Johnson, Rachel; Coll, Elisabeth; Jansen, Nichon; Antoine, Corinne; Procaccio, Francesco; Lynch, Nessa; Foss, Stein; Colenbie, Luc; Fryda, Preysmil; Jushinskis, Janis; Bolotinha, Catarina; et al.
Abstract : Introduction: Donation after circulatory death (DCD) has become an accepted practice in many countries and remains a focus of intense interest in the transplant community due to its potential to increase the donor pool. In 2011, the European Committee on Organ Transplantation (CD-P-TO) of the Council of Europe (COE) published a study on the situation of DCD in Europe. Since then, the scene has enormously changed, with more countries initiating or developing DCD programmes and with practices evolving as new evidence becomes available. The aim of the present study is to provide an updated description of the current situation of DCD in COE member states. Material and Methods: The CD-P-TO designed and agreed upon a specific questionnaire. Each representative collected the requested information from official sources. Data was returned to the CD-P-TO Secretariat for subsequent quality control and analysis. Results: Thirty-one countries, (66%) completed the survey. Sixteen countries declared not having developed any DCD activity, because of legislative obstacles (31%), no regulatory framework (50%), lack of technical expertise (44%) and/or insufficient organizational capabilities (25%). Of these countries, 5 stated interest in developing a controlled DCD (cDCD) programme and 4 in developing both cDCD and uncontrolled DCD (uDCD) programmes, while 7 were not planning to develop any DCD activity. DCD was practiced in 15 countries: 7 had both cDCD and uDCD programmes, 3 only cDCD and 5 only uDCD. During 2008-2016, the activity progressively increased, with the highest activity being described in the United Kingdom, the Netherlands, Belgium (mainly controlled), France and Spain (mainly uncontrolled). The number of DCD organs transplanted increased from 1039 in 2008 to 3440 in 2016. In total, 12, 115 DCD organs were transplanted over the study period (8, 972 kidneys, 1, 943 livers, 782 lungs, 404 pancreata and 14 hearts). For cDCD procedures, 6 had specific provisions in national legislation, but all 10 countries declared having national guidance. In 7 countries the pre-mortem administration of substances is allowed practiced, whereas pre-mortem cannulation is allowed in 3 countries but only practiced in 2. Normothermic abdominal perfusion for in situ preservation of organs is allowed in 8 countries but only practiced in 5.Finally, updated data on post-transplant outcomes of patients who received DCD organs show better outcomes for grafts obtained from cDCD versus uDCD donors. Conclusion: DCD is becoming increasingly accepted and performed in Europe, importantly contributing to the number of organs available and providing acceptable post-transplantation outcomes. This study will allow countries to benchmark their programmes and clinical practices and foster discussion on the ethical and technical obstacles to this type of donation in a European common framework of understanding.